Implications of Endectocide Residues on the Survival of Aphodiine Dung Beetles: A Meta‐Analysis. (17th March 2020) - Finch, Domhnall; Schofield, Henry; Floate, Kevin D.; Kubasiewicz, Laura M.; Mathews, Fiona
Abstract: It is often difficult to compare studies examining the effects of endectocides on dung fauna because of different experimental approaches, for example, active ingredients (eprinomectin, doramectin, ivermectin, moxidectin) and formulations (injectable, pour‐on, spiked). To gain a better understanding, we performed a quantitative meta‐analysis using 22 studies to assess the overall effect of endectocide residues on the occurrence (presence or absence) and abundance of aphodiine dung beetles. Our results document a positive effect on the occurrence of adult beetles, indicating that adults tend to be attracted to dung with residues. Conversely, larvae are less likely to occur in the presence of residues. Thus, either adults that colonize dung with residues do not lay eggs or, more likely, the larvae that hatch from these eggs die early in development. Abundance of adult and larval stages was shown to be significantly reduced in dung containing residues. When individual endectocides were compared, only ivermectin demonstrated a significantly negative effect on the abundance of both adults and larvae, possibly owing to a small sample size for other agents. In laboratory studies, only dung "spiked" with endectocides reduced the abundance of larvae, whereas during field research, only pour‐on applications were shown to reduce the abundance of larvae. The present study further documents the nontarget effects of endectocide residues on dung‐dwelling organisms, provides robust evidence on the consequences of different application methods, and emphasizes the need for standardized methodological techniques in future studies. Environ Toxicol Chem 2020;39:863–872. © 2020 SETAC